A general-equilibrium asset-pricing approach to the measurement of nominal and real bank output - J. Christina Wang; Susanto Basu; John G. Fernald (Federal Reserve Bank of Boston, 2004)
This paper addresses the proper measurement of financial service output that is not priced explicitly. It shows how to impute nominal service output from financial intermediaries' interest income and how to construct price indices for those financial services. We present an optimizing model with financial intermediaries that provide financial services to resolve asymmetric information between borrowers and lenders. We embed these intermediaries in a dynamic, stochastic, general-equilibrium model where assets are priced competitively according to their systematic risk, as in the standard consumption capital-asset-pricing model. In this environment, we show that it is critical to take risk into account in order to measure financial output accurately. We also show that even using a risk-adjusted reference rate does not solve all the problems associated with measuring nominal financial service output. Our model allows us to address important outstanding questions in output and productivity measurement for financial firms, such as: (1) What are the correct reference rates to use in calculating bank output? In particular, should they take account of risk? (2) If reference rates need to be risk-adjusted, does it mean that they must be ex ante rates of return? (3) What is the right price deflator for the output of financial firms? Is it just the general price index? (4) When-if ever-should we count capital gains of financial firms as part of financial service output?
Keywords: G2; G21; E01; E44; 330